Elections and de facto Expenditure Decentralization in Canada - Mario Jametti; Marcelin Joanis (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper empirically investigates the underlying determinants of expenditure decentral- ization, based on the predictions of a new political economy model of partial decentralization. The analysis is based on an agency model, in which two levels of government are involved in the provision of a public good and voters are imperfectly informed about each government's contribution to the good, creating a shared accountability problem. Under shared expenditure responsibility, the degree of decentralization is endogenous and depends on the relative politi- cal conditions prevailing at each level of government. Consistent with the model's predictions, empirical results from a panel of Canadian provinces show that decentralization in a province increases with the electoral strength of the provincial government and decreases with the electoral strength of the federal government, in addition to being affected significantly by the partisan affiliation of both levels of government. A series of alternative empirical specifications, including an IV regression exploiting campaign spending data, are presented to assess the robustness of these results.
Keywords: R50; H77; D72; 330; fiscal decentralization; fiscal federalism; vertical interactions; partial decentralization; elections